2021
DOI: 10.3389/fendo.2021.650328
|View full text |Cite
|
Sign up to set email alerts
|

FKBPL and SIRT-1 Are Downregulated by Diabetes in Pregnancy Impacting on Angiogenesis and Endothelial Function

Abstract: Diabetes in pregnancy is associated with adverse pregnancy outcomes including preterm birth. Although the mechanisms leading to these pregnancy complications are still poorly understood, aberrant angiogenesis and endothelial dysfunction play a key role. FKBPL and SIRT-1 are critical regulators of angiogenesis, however, their roles in pregnancies affected by diabetes have not been examined before in detail. Hence, this study aimed to investigate the role of FKBPL and SIRT-1 in pre-gestational (type 1 diabetes m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 79 publications
0
24
1
Order By: Relevance
“…Since the placenta is a highly vascularized organ that supplies nutrients, growth factors, oxygen, hormones, and immune mediators to the fetus, all molecules of the angiogenic axis are tightly regulated throughout pregnancy. However, as mentioned before, clinical examination of GDM placentae shows increased villous vascularity often associated with thickened immature villi capillaries [ 20 , 21 , 24 ]. Diverse experimental evidence indicate that hyperglycemia promotes angiogenesis, vasoconstriction, and a higher vessel permeability [ 233 , 234 , 235 , 236 , 237 , 238 ].…”
Section: Endovascular Changes In Gdm: Endothelial Dysfunction and Overstimulation Of Placental Angiogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Since the placenta is a highly vascularized organ that supplies nutrients, growth factors, oxygen, hormones, and immune mediators to the fetus, all molecules of the angiogenic axis are tightly regulated throughout pregnancy. However, as mentioned before, clinical examination of GDM placentae shows increased villous vascularity often associated with thickened immature villi capillaries [ 20 , 21 , 24 ]. Diverse experimental evidence indicate that hyperglycemia promotes angiogenesis, vasoconstriction, and a higher vessel permeability [ 233 , 234 , 235 , 236 , 237 , 238 ].…”
Section: Endovascular Changes In Gdm: Endothelial Dysfunction and Overstimulation Of Placental Angiogenesismentioning
confidence: 99%
“…Dr. Lana Mc-Clements found GDM placentae have a decreased expression of the anti-angiogenic protein sirtuin 1 (SIRT-1), which may help to explain the increased vascularized network observed in GDM placentae. Additionally, they cultured a trophoblast cell line (obtained from first trimester/choriocarcinoma) under conditions of hyperglycemia (25 mM) and hypoxia (2.5 and 6.5% O 2 ), and observed a downregulated expression of the anti-angiogenic proteins FK 506 binding protein-like (FKBLP) and SIRT-1 [ 24 ]. These results support the hypothesis that hyperglycemia and lower oxygen tension alter the balance of factors that regulate angiogenesis in the placenta, leading to vascular dysfunction and possibly the development of preeclampsia.…”
Section: Endovascular Changes In Gdm: Endothelial Dysfunction and Overstimulation Of Placental Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to those observations, only the expression SIRT-1 gene was significantly downregulated in patients with GDM compared to the controls [176]. Moreover, the high FKBPL expression in HUVECs, evoked by plasmid vector transfection, was associated with a reduction in tubule formation and could be potentially responsible for endothelial dysfunction in vivo [176]. Di Tomo et al reported that HUVECs collected from women with GDM presented alterations in mitochondrial membrane potential and antioxidant response compared with cells obtained in controls.…”
Section: Assessment Of Endothelial Function In In Vitro Conditionsmentioning
confidence: 89%